Cormac McCarthy’s The Road : Rewriting the Myth of the American West - Aitor Ibarrola-Armendariz (European Journal of American Studies)
This article argues that Cormac McCarthy’s latest novel, The Road (2006), marks a clear departure from the interests and aesthetics he showed in his earlier works of fiction. Apart from the fact that the Rhode Island-born writer embarks for a first time in his long career on a popular sci-fi sub-genre such as the post-apocalyptic novel, the book exhibits a number of thematic, structural, and stylistic patterns which differ quite radically from those found in his earlier novels. Most likely influenced by some recent events that have deeply shaken the country and others affecting his personal life, McCarthy can be seen to abandon the landscapes and vernacular rhythms that had become the staple of his artistic performance. By comparing The Road to some of his earlier fiction, the article attempts to establish where those elements of discontinuity become most apparent. In spite of his deadpan naturalism and rather laconic language use, the author manages to keep his readers on their toes thanks to the novel’s much accomplished suspense concerning the fate of the two protagonists. The denouement of the story also strikes those familiar with his fiction as unusual. Still, the second half of the article reveals that, despite all these departures from his previous aesthetics and philosophical wanderings, there are also a number of elements in The Road that speak of his commitment to some values and myths that have contributed to his reputation and fame.